2021
DOI: 10.30574/wjarr.2021.10.3.0241
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging activity and phytochemical screening of the leaf extract of Synsepalum dulcificum (Schumach. & Thonn.) Daniell

Abstract: Antioxidants are chemicals that possess bioactive constituents which usually allow them to fight against free radicals. Antioxidant and phytochemicals properties of the leaves of Synsepalum dulcificum were investigated using ethyl-acetate, ethanol and methanol extracts. 2, 2-diphenyl-picrylhydrazyl (DPPH) scavenging activity, total antioxidant activity, ferric reducing antioxidant power (FRAP), total flavonoid and the total phenolic content was carried out. The phytochemical screening assay was done on the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The leaf and fruit extracts of Synsepalum dulcificum (Schumach. & Thonn) Daniell contained carbohydrate 40.38 and 17.44%, crude fibre 17.58 and 3.63%, crude protein 8.42 and 10.46%, crude fat 1.97 and 2.32%, ash content 2.87 and 3.95% and moisture content 28.78 and 62.40% respectively) (Awotedu & Ogunbamowo, 2019a;Awotedu & Ogunbamowo, 2019b). The proximate analysis of the leaves extracts of Synsepalum dulcificum (Schumach.…”
Section: Chemopharmacological Potential Of Synsepalum Dulcificummentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf and fruit extracts of Synsepalum dulcificum (Schumach. & Thonn) Daniell contained carbohydrate 40.38 and 17.44%, crude fibre 17.58 and 3.63%, crude protein 8.42 and 10.46%, crude fat 1.97 and 2.32%, ash content 2.87 and 3.95% and moisture content 28.78 and 62.40% respectively) (Awotedu & Ogunbamowo, 2019a;Awotedu & Ogunbamowo, 2019b). The proximate analysis of the leaves extracts of Synsepalum dulcificum (Schumach.…”
Section: Chemopharmacological Potential Of Synsepalum Dulcificummentioning
confidence: 99%
“…The preliminary phytochemical analysis showed that Synsepalum dulcificum (Schumach. & Thonn) Daniell pulp contained saponin, flavonoids, tannin, alkaloids, glycosides, phenol, resins, terpenoids, steroids, and anthraquinones and cyanogenic glycosides (Ibrahim et al, 2020;Awotedu et al, 2021). The isolated compounds from Synsepalum dulcificum (Schumach.…”
Section: Chemopharmacological Potential Of Synsepalum Dulcificummentioning
confidence: 99%